L'affaire de Justine et l'échec de la clandestinité. (July 2014) - Warman, Caroline
<x content-type="archive" xml:space="preserve">Abstract</x> This article reviews the documents in the campaign to destroy the anonymity around Justine by repeatedly denouncing Sade as its author. The campaign lasted from 1798 to 1801 and involved increasingly violent denunciations on both sides, appearing in at least three newspapers and also surfacing in a now little-known verse satire by Joseph Despaze. Sade's ripostes were printed in newspapers, in his essay, Idée sur les romans, and also in a pamphlet of exemplary ferocity. We analyse the multiple exchanges between Sade and his opponents, and relate them to the theme of denunciation in the French Revolution more widely.